THE EFFECTS OF ENTREPRENEURSHIP EDUCATION AND PERSONALITY TRAITS ON ENTREPRENEURIAL INTENTION AMONG IBA STUDENTS - Tulenan, Charles B.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: This study is informed by high number of unemployment that have been a serious problem in Indonesia.Government programs to reduce unemployment have not been able to reduce unemployment significantly because for the large population and population growth are increasing, not accompanied by an increase in employment and possibility of making entrepreneurship asa carrier choice affected by entrepreneurship education and their personality. This study purpose isinvestigated the relationship that exists between offering entrepreneurship education, personality traits and students intention to becomeentrepreneurs in IBA. The population of the study were all IBA students. Convinience sampling was use. The data was gathered using Likert scale, ranging from stronglyagreed to strongly disagree. SPSS version 16, descriptive statistics and Pearson correlation were used in theanalysis of the data. The results showed that the students agreed that there is positive relationship between Entrepreneurship education and and Personality Traits on their intention to become entrepreneurs. The correlation resultsalso showed that, there is a positive relationship. Don’t ever give up to start a new business, its better to be a boss in a small company rather than an employee in a big company, success need a step Keywords : entrepreneurship education, entrepreneurship, personality traits,entrepreneurship intention.